Well-being of Older People (WOOP): Quantitative validation of a new outcome measure for use in economic evaluations. (August 2020) - Hackert, Mariska Q.N.; van Exel, Job; Brouwer, Werner B.F.
Abstract: There is a need for comprehensive measures to evaluate the benefits of health and social care services for older people. The newly developed Well-being of Older People measure (WOOP) aims to capture all aspects that older people find important to their well-being. This study explores the validity and test-retest reliability of the WOOP. Between December 2017 and January 2018, an online survey was used to retrieve data from 1113 people aged 65 years and older in the Netherlands. Regression analyses on Cantril's Ladder scores were conducted to explore the relative importance of the items of the WOOP. Dimensionality was checked using exploratory factor analysis. Convergent and discriminant validity were investigated by relating the WOOP to several measures of health and well-being. Test-retest reliability was examined using data from 269 respondents that participated in a second online survey, distributed one week after the first. The items of the WOOP were significantly associated with Cantril's Ladder scores. When regressed simultaneously this was still true for all but the 'social contacts' item and one level of the 'acceptance and resilience' item. The dimensionality analysis revealed three factors, of which two included items of the WOOP and the EQ-5D-5L and the third only items of the WOOP. The WOOP correlated moderately to highly with physical health, and (very) highly with (mental) health and well-being measures. The test-retest reliability in terms of ICC was high, whereas the kappa for the items was fair to good, except for two items. Overall, the WOOP seems to capture aspects relevant to the well-being of older people adequately, and the results of first validity and reliability tests were satisfactory. Before the WOOP can be used in economic evaluations, further validation in a variety of health and social care settings is recommended, and utility weights need to be determined. Highlights: First quantitative validation of the Well-being of Older People measure (WOOP). Which captures a comprehensive set of well-being domains relevant to older people. Validity and test-retest reliability were satisfactory among Dutch older people. The WOOP appears to be a promising outcome measure for use in economic evaluations.